Severe malarial thrombocytopenia: a risk factor for mortality in Papua, Indonesia. - Lampah, D; Yeo, T; Malloy, M; Kenangalem, E; Douglas, N; Ronaldo, D; Sugiarto, P; Simpson, J; Poespoprodjo, J; Anstey, N; Price, R (Oxford University Press, 2015)
BACKGROUND: The significance of thrombocytopenia to the morbidity and mortality of malaria is poorly defined. We compared the platelet counts and clinical correlates of patients with and those without malaria in southern Papua, Indonesia. METHODS: Data were collated on patients presenting to a referral hospital between April 2004 and December 2012. RESULTS: Platelet measurements were available in 215 479 patients (23.4%), 66 421 (30.8%) of whom had clinical malaria. Patients with Plasmodium falciparum monoinfection had the lowest platelet counts and greatest risk of severe thrombocytopenia (platelet count, <50,000 platelets/µL), compared with those without malaria (adjusted odds ratio [OR], 6.03; 95% confidence interval [CI], 5.77-6.30]). The corresponding risks were 5.4 (95% CI, 5.02-5.80) for mixed infections, 3.73 (95% CI, 3.51-3.97) for Plasmodium vivax infection, and 2.16 (95% CI, 1.78-2.63) for Plasmodium malariae infection (P<.001). In total, 1.3% of patients (2701 of 215 479) died. Patients with severe malarial anemia alone (hemoglobin level, <5 g/dL) had an adjusted OR for death of 4.93 (95% CI, 3.79-6.42), those with severe malarial thrombocytopenia alone had an adjusted OR of 2.77 (95% CI, 2.20-3.48), and those with both risk factors had an adjusted OR of 13.76 (95% CI, 10.22-18.54; P<.001). CONCLUSIONS: Severe thrombocytopenia identifies both children and adults at increased risk of death from falciparum or vivax malaria, particularly in those with concurrent severe anemia.